Jurists and Jurisprudence in Medieval Italy Texts and Contexts - Cavallar, Osvaldo; Kirshner, Julius 1939- (Toronto University of Toronto Press, 2020)
This unique collection makes available, for the first time, translations of medieval Italian jurisprudence, including commentaries, tracts, and legal opinions by leading jurists.
Cover -- Copyright -- Contents -- Preface -- Acknowledgments -- Abbreviations -- Short Titles -- Introduction -- 1. Professors and Students -- 1. Foundations -- 1.1. The Constitution Habita of Emperor Frederick I Barbarossa (1155/58) -- 1.2. Accursius's Glosses to the Constitution Habita -- 1.3. Students as Citizens in the Statutes of Modena (1327) -- 2. "We Give You the Licence to Teach Here and Everywhere" -- 2.1. Baldus de Ubaldis, Consilium on the Studium Generale of Milan (ca. 1393−1396) -- 3. Privileges of Doctors and Students -- 3.1. Simon of Borsano, Privileges of Doctors and Students (1361−1370) -- 4. How to Teach and Study Canon and Civil Law -- 4.1. Franciscus de Zabarellis, How to Teach and Study Canon and Civil Law (ca. 1410) -- 5. The Many Dwelling Places of Civil Wisdom -- 5.1. Bartolus of Sassoferrato, Oration on Conferring the Doctorate of Law -- 6. Death Benefits -- 6.1. Consilium of Jacobus Niccoli (1400) -- 7. Hired Hands -- 7.1. Azo, Hiring (1208−1210) -- 7.2. Rainerius of Perugia, Leasing out a Work to Be Copied (1242) -- 7.3. Salatiele, Copyists, and Other Persons Obligating Themselves to Perform Services [Contract and Glosses] (1248−1254) -- 7.4. Rolandinus de Passegeriis, Hiring Another Person's Services to Copy a Work (1273) -- 8. Law Students' Books -- 8.1. Baldus de Ubaldis, Consilium [I] (ca. 1393-1396) -- 8.2. Baldus de Ubaldis, Consilium [II] (ca. 1393-1396) -- 9. "Many Books" -- 9.1. Oldradus de Ponte, Whether It Is Advantageous to Have Many Books (ca. 1320s) -- 10. Nobility, Usefulness, and Origin of Law -- 10.1. Doctoral Oration (ca. 1450) -- 2. Legal Profession -- 11. Advocates -- 11.1. Guilelmus Durantis, Mirror of Law (ca. 1284−1289) -- 12. Fees -- 12.1. Azo, Quaestio disputata -- 13. Proof of a Doctoral Degree -- 13.1. Certifying a Judge's Doctoral Degree in Florence (1374).
Description based on publisher supplied metadata and other sources
Keywords: Common law-History-Sources-Italy-To 1500; Jurisprudence-History-Sources-Italy-To 1500; Law-Sources-Italy-To 1500; Electronic books; Italy